2008
DOI: 10.1538/expanim.57.453
|View full text |Cite
|
Sign up to set email alerts
|

Effecs of Cypermethrin on Some Biochemical Changes in Rats: The Protective Role of Propolis

Abstract: SOD and CAT, liver SOD and GSH-Px, kidney SOD and brain SOD, CAT and GSH-Px

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
5
27
0
Order By: Relevance
“…Plasma TG also increased significantly in their study. TG levels in our study increased progressively until the end of treatment, as has been observed during acute CYP intoxication reported in other studies at higher doses (Eraslan et al, 2008). In relation to albumin, an acute phase protein, our results indicated that doses of CYP and DEL which were above permissible limits, caused a decrease albumin levels.…”
Section: Discussionsupporting
confidence: 87%
“…Plasma TG also increased significantly in their study. TG levels in our study increased progressively until the end of treatment, as has been observed during acute CYP intoxication reported in other studies at higher doses (Eraslan et al, 2008). In relation to albumin, an acute phase protein, our results indicated that doses of CYP and DEL which were above permissible limits, caused a decrease albumin levels.…”
Section: Discussionsupporting
confidence: 87%
“…However, in the propolis+CA group, the plasma urea level demonstrated to be significantly decreased compared with the levels in the CA group. Eraslan et al (27) have reported similar effects. In both groups administered with propolis, increase in uric acid levels may be related to either the increase in protein degradation, which is involved in uric acid formation, or the influence of propolis on the kidneys.…”
Section: Discussionmentioning
confidence: 76%
“…Decreased activity of SOD and CAT has been reported in rats exposed to pyrethroids (Eraslan, Kanbur, and Silici 2008;Hussein, Elnaggar, and Al-Dailamy 2012). Significant decrease in the activity of GPx (Raina et al 2009;Dubey, Raina, and Khan 2012;Dubey, Khan, and Raina 2013;Khan et al 2013b;Dar et al 2013) and GST (Singh, Saxena, and Sharma 2009;Dar et al 2013) has also been reported with several pyrethroids in various tissues.…”
Section: Discussionmentioning
confidence: 95%